A field guide for on-farm experimentation - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
A field guide for on-farm experimentation by H J W Mutsaers, G K Weber, P Walker and N M Fisher 1997 235pp ISBN 978 131 125 8credit points 20CTA